Effect of fermented pineapple silage on growth and stress tolerance of Penaeus monodon post-larvae - CHEENY A. HONCADA; JAY B. LEMOSNERO; BRYLLE P. NAMUAG; KATHLEEN P. CANDOLE; FIONA L. PEDROSO (Smujo International, 2025)
Abstract. Honcada CA, Lemosnero JB, Namuag BP, Candole KP, Pedroso FL. 2025. Effect of fermented pineapple silage on growth and stress tolerance of Penaeus monodon post-larvae. Asian J Agric 9: 533-541. The incorporation of pineapple waste into animal feeds has been previously reported; however, its potential application in aquaculture remains underexplored. In particular, the use of liquid-fermented pineapple silage derived from industrial processing has not been documented. This study investigated the effects of liquid fermented pineapple silage (LFPS) and yeast-enriched LFPS (LFPS+Yeast), applied by spraying onto commercial feed, as alternative feed additives for post-larval tiger shrimp (Penaeus monodon). Results demonstrated that the inclusion of LFPS+Yeast significantly improved weight gain (p < 0.05) in P. monodon post-larvae, with the highest mean weight gain observed in the LFPS+Yeast group (62.57?±?3.43?mg), followed by LFPS (53.37?±?5.63?mg), and the control (39.30?±?3.40?mg). A similar trend was observed in growth rate (GR) (p < 0.05). Although the specific growth rate (SGR) did not differ significantly among treatments (p > 0.05), the LFPS+Yeast group exhibited the highest SGR (11.30?±?0.52%), followed by LFPS (10.97?±?0.52%) and the control (9.84?±?0.35%). No significant differences were found in survival or stress tolerance; however, both LFPS+Yeast and LFPS treatments showed improved survival rates (80.00?±?1.40% and 73.11?±?2.50%, respectively) compared to the control (67.56?±?7.45%), as well as enhanced stress response. These findings suggest that LFPS and LFPS+Yeast have strong potential as sustainable feed additives in shrimp aquaculture, offering a means of waste valorization while promoting improved growth and resilience in P. monodon.